Gambaran Self-disclosure pada Mahasiswa di Second Account Instagram - Malinda Syafrina; Tutut Chusniyah (Universitas Negeri Malang, 2025)
Self-disclosure is an effort to introduce oneself to others with the intention of building closer relationships. In the digital era, social media platforms such as Instagram have become popular spaces for self-expression and sharing personal information, especially among university students. However, an interesting phenomenon has emerged where some students choose to use a second, more private account (often referred to as a second account) as a space for personal expression. The aim of this study is to understand the subjective experiences of students engaging in self-disclosure on their second Instagram accounts. The research focuses on uncovering the meaning, motivations, and emotions students experience when sharing and expressing themselves through these more private accounts. A qualitative approach was used, employing in-depth interviews with students who actively use second accounts. The findings reveal that second accounts are perceived as safer and more comfortable spaces for students to pour out their hearts, share their concerns, and express their emotions more honestly, even though they still maintain certain boundaries of privacy in their social media use. AbstrakSelf-disclosure atau keterbukaan diri merupakan sebuah upaya untuk mengenalkan diri sendiri kepada orang lain dengan maksud untuk lebih dekat dengan orang lain. Di era digital, media sosial seperti Instagram menjadi ruang populer untuk mengekspresikan diri dan berbagi informasi pribadi, terutama di kalangan mahasiswa. Namun, terdapat fenomena menarik di mana sebagian mahasiswa memilih menggunakan akun kedua (second account) yang lebih privat sebagai tempat untuk menyalurkan ekspresi diri. Tujuan dari penelitian ini yaitu untuk memahami pengalaman subjektif mahasiswa dalam melakukan self-disclosure di second account Instagram. Penelitian ini difokuskan untuk mengungkap makna, motivasi, serta perasaan yang dialami mahasiswa ketika mereka membagikan dan mengekspresikan diri melalui akun yang lebih tertutup. Pendekatan yang digunakan adalah kualitatif dengan teknik wawancara mendalam kepada mahasiswa yang aktif menggunakan second account. Hasil penelitian menunjukkan bahwa second account menjadi ruang yang dirasa lebih aman dan nyaman bagi mahasiswa untuk mencurahkan isi hati, berbagi keresahan, serta mengekspresikan emosi secara lebih jujur, meskipun mereka tetap menjaga batas privasi dalam bermedia sosial.